(2-Hydroxyethyl)(propyl)azanium2-[(2-carboxyphenyl)disulfanyl]benzoate monohydrate - Broker, G.A.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
With the exception of the terminal hydroxy group [N-C-C-O = 53.8 (5)degrees], the cation of the title salt hydrate, C(5)H(14)NO(+)center dot C(14)H(9)O(4)S(2)(-center dot)H(2)O, is a straight chain. A twisted conformation is found for the anion [C-S-S-C = -87.44 (16)degrees]. In the crystal, the anions self-assemble into a helical supramolecular chain via charge-assisted O-H center dot center dot center dot O(c) hydrogen bonds. These chains are connected into a three-dimensional network via N-H center dot center dot center dot O(c), N-H center dot center dot center dot O(w), O(h)-H center dot center dot center dot O(cb), and O(w)-H center dot center dot center dot O(c) hydrogen-bonding interactions (c = carboxylate, w = water, h = hydroxy and cb = carbonyl).